2022
DOI: 10.1177/21650799211067927
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hearing Protection Device Noise Attenuation Through Fit-Testing in an Occupational Health Clinic

Abstract: Background: Occupational noise-induced hearing loss (NIHL) is the second most common medical disability for military veterans and accounts for 24% of all hearing loss in the United States. Hearing loss negatively affects health and billions of dollars are spent annually for direct and indirect medical costs and lost work productivity. Proper hearing protection device (HPD) fit can prevent NIHL. Quantitative fit-testing systems to determine personal attenuation rates (PARs) are available, but not widely utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…isolating the source of noise with temporal implementations, and even stopping the production process to perform activities in the contaminated area. Unexpectedly, the solutions may be obvious and simple, such as the use of protectors, isolating the noise sources, and avoiding machinery overload [42]. However, the application and correct use of these accessories also present a significant challenge for the local industry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…isolating the source of noise with temporal implementations, and even stopping the production process to perform activities in the contaminated area. Unexpectedly, the solutions may be obvious and simple, such as the use of protectors, isolating the noise sources, and avoiding machinery overload [42]. However, the application and correct use of these accessories also present a significant challenge for the local industry.…”
Section: Methodsmentioning
confidence: 99%
“…To address this challenge and to ensure the health and safety of workers exposed to noise contamination, engineers and industrial hygienists have developed various methods and systems to isolate and reduce indoor noise, effectively mitigating noise source of noise with temporal implementations, and even stopping the production process to perform activities in the contaminated area. Unexpectedly, the solutions may be obvious and simple, such as the use of protectors, isolating the noise sources, and avoiding machinery overload [42]. However, the application and correct use of these accessories also present a significant challenge for the local industry.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, one of the main limitations comes from the hearing protection devices. It has been shown that if the users are not properly trained on how to use them or if they are not placed properly, their efficiency varies drastically [58,59]. This is why Hayes et al [58] recommend the implementation of training and fit tests for hearing protection users.…”
Section: Limitationsmentioning
confidence: 99%
“…It has been shown that if the users are not properly trained on how to use them or if they are not placed properly, their efficiency varies drastically [58,59]. This is why Hayes et al [58] recommend the implementation of training and fit tests for hearing protection users. Kozlowski et al [60] brought up the idea of a simple and affordable tester to verify the placement of earplugs.…”
Section: Limitationsmentioning
confidence: 99%